The Influence of The Balanced Scorecard Implementation and Earnings Management on Financial Performance: Intellectual Capital and Customer Satisfaction Used as the Moderators - Chien , Yung-Chieh; Ting, Keng-Sheng (Asian Journal of Empirical Research, 2014)
The main purpose of this research is to understand the influence of the company’s implementation of the Balanced Scorecard (BSC) and earnings management on financial performance, and executives of listed electronics companies (above the section chief) in Taiwan were research subjects. This research adopts database of Taiwan Economic Journal (TEJ) and TEAMS for data collection and uses HLM3 in analyzing the collected data. Research findings indicate the BSC implementation and earnings management by listed electronics companies in Taiwan show significant positive influence on financial performance, while intellectual capital and customer satisfaction have moderating effects.